2023
DOI: 10.3390/ijms241814216
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of WUSCHEL-Related Homeobox Gene Family in Sacred Lotus (Nelumbo nucifera)

Gui-Zhen Chen,
Jie Huang,
Zhi-Cong Lin
et al.

Abstract: WUSCHEL-related homeobox (WOX) is a plant-specific transcription factor (TF), which plays an essential role in the regulation of plant growth, development, and abiotic stress responses. However, little information is available on the specific roles of WOX TFs in sacred lotus (Nelumbo nucifera), which is a perennial aquatic plant with important edible, ornamental, and medicinal values. We identified 15 WOX TFs distributing on six chromosomes in the genome of N. nucifera. A total of 72 WOX genes from five specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…It was found that members of maize, barley and Arabidopsis as herbaceous plants appeared to cluster with each other, such as AtWOX11 and AtWOX12 in Arabidopsis at the Intermediate Clade, HvWOX7 and HvWOX8 in barley, ZmWOX21 and ZmWOX23 in maize. Similarly, clustering phenomena have also been observed in Nelumbo nucifera, such as NnWOX6 and NnWOX9 , NnWOX1 and NnWOX4 [ 38 ]. Previous studies have found that the relationship between GmWOXs and PvWOXs is closer, possibly due to the fact that lotus root and soybean both belong to the legume family [ 5 ].…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…It was found that members of maize, barley and Arabidopsis as herbaceous plants appeared to cluster with each other, such as AtWOX11 and AtWOX12 in Arabidopsis at the Intermediate Clade, HvWOX7 and HvWOX8 in barley, ZmWOX21 and ZmWOX23 in maize. Similarly, clustering phenomena have also been observed in Nelumbo nucifera, such as NnWOX6 and NnWOX9 , NnWOX1 and NnWOX4 [ 38 ]. Previous studies have found that the relationship between GmWOXs and PvWOXs is closer, possibly due to the fact that lotus root and soybean both belong to the legume family [ 5 ].…”
Section: Resultsmentioning
confidence: 92%
“…To investigate the structural diversity of VdWOX genes, the distribution of exons and introns was analyzed. Gene structure analysis revealed that the number of introns among members of the VdWOX gene family ranges from 1 to 3, a phenomenon also observed in lotus and soybean [ 5 , 38 ]. Specifically, SVdWOX9 , VdWOX10 , VdWOX11 and VdWOX12 contain two exons, VdWOX2 and VdWOX8 contain four exons, while the remaining six members contain three exons each (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of WOX members varies in these plants. Although genome-wide identification of the WOX members in lotus were preliminarily studied [ 39 ], the regulatory interactions of NnWOXs genes need further investigation. With increasing genomics research on lotus [ 30 , 48 ], the Nelumbo Genome Database provided a great platform to investigate the whole-genome analysis of transcription factors [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several transcription factor families were identified in lotus, such as MADS-box [ 36 ], WRKY [ 37 ], and YABBY [ 38 ]. Although a previous study conducted a preliminary analysis of the WOX gene family in lotus [ 39 ], the interactions of WOX genes is still largely unknown. Therefore, we describe WOX genes systematically in N. nucifera and construct the co-expressed networks to find vital interactions regarding NnWOX genes during plant growth and development.…”
Section: Introductionmentioning
confidence: 99%